Characteristics of the Organizational and Creative Development of Theaters in the Ferghana Region (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the distinctive organizational and creative developments of theaters in the Fergana region, with a specific focus on the Kokand Music and Drama Theater during the early stages of the European Uzbek theater's evolution. The analysis centers on the role of the creative team in shaping the theater's repertoire.